MANAJEMEN PERENCANAAN PENGELOLAAN SPORT CENTER DI KABUPATEN KUDUS - Alya Ega Suciana; Fatona . Suraya (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2022)
Kudus Regency Sport Center is a sports activity center area for athletes and the community in Kudus Regency. This study aims to determine how the management of Sport Center management planning in Kudus Regency is based on the fundamental function of planning management (planning). The planning indicators that will be achieved in this research are (1) what is the goal of building a Sport Center; (2) what is the policy at the Sport Center; (3) how the strategies used in the management; (4) how are human resources in management; and (5) where are the sources of funds used for management. This study uses a qualitative descriptive research type. The data collected using the method of observation, interviews, and documentation. The subjects in this study were managers, employees, and users of the Sport Center. By using data analysis techniques carried out through data collection, data reduction, data presentation, and drawing conclusions. The results showed that the management planning of the Sport Center in Kudus Regency was still lacking, in its management it did not have a special strategy for each area/building and only relied on funding sources from APBD II.